Impacts of sun glint off ice clouds on DSCOVR EPIC cloud products - Várnai, Tamás; Marshak, Alexander; Kostinski, Alexander B.; Yang, Yuekui; Zhou, Yaping (IEEE, 2024)
The Earth Polychromatic Camera (EPIC) onboard the Deep Space Climate Observatory (DSCOVR) spacecraft observes the sunlit face of the Earth from a distance of about one-and-a-half million kilometers. Several studies demonstrated that EPIC images often feature sun glint from water surfaces and from horizontally oriented ice crystals occurring inside clouds. This study presents a statistical analysis of a yearlong EPIC dataset to gain insights into sun glints and their impacts on satellite measurements of cloudiness and cloud properties. The first results discussed demonstrate that over land, the observed glints indeed come mainly from ice clouds and not from small water bodies. Subsequent results reveal that sun glints affecting EPIC observations (especially at 388 nm) greatly increase the likelihood and sensitivity of cloud detection, particularly of the elusive thin and small ice clouds. Finally, the results indicate that sun glints often cause spurious increases in the cloud optical thickness and altitude values in the operational EPIC cloud product. Insights into the frequency, magnitude, and causes of glint effects and suggestions for future work are also provided.
Keywords: Clouds; remote sensing; Atmosphere; clouds; Crystals; Earth; ice; Ice clouds; Sea surface; Sun; Surface roughness